Governance and Public Participation - Siewert, Stephanie; Kieslich, Katharina; Braun, Matthias; Dabrock, Peter (Springer Science and Business Media B.V., 2023)
The chapter discusses different objectives of public participation in synthetic biology and suggests six focus areas across all governance dimensions, hard law, soft law, education, research impact, and research infrastructure, to design effective participation in synthetic biology. The authors identified three focus areas in participation—communication, representation, and evaluation—that are of particular importance for ensuring trust and justice as core values of SB governance. In addition, three intersecting focus areas in governance provide incentives for decision-making: resources, training, and data management. Furthermore, the authors highlight the question of responsibility as an area that requires special attention.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Data Management; Focus Areas; Communication; Formats; Objectives of Participation; Representation; Evaluation; Resources; Training; Responsibility